Examining the determinants of cloud computing adoption among the Kuwaiti SMEs - Alkandari, Sulaiman M.; Husin, Mohd. H.; Abdullah, Nasuha L.; Baharudin, Ahmad S.; Wahdain, Esmat A. (Edelweiss Applied Science and Technology, 2025)
Cloud computing (CC) has emerged as a promising technology for supporting business operations, particularly for small and medium enterprises (SMEs) that face financial and technical resource constraints. Despite its potential benefits, the level of cloud computing adoption (CCA) among SMEs in Kuwait remains relatively low. This study aims to investigate the factors influencing the intention to adopt cloud computing (IACC) among Kuwaiti SMEs by employing a research model grounded in the Technology–Organization–Environment (TOE) framework. A quantitative methodology was adopted, and data were collected through a survey of SME owners and managers in Kuwait. The proposed model examines the effects of relative advantage, security concerns, top management support, competitive pressure, trading partners’ pressure, and entrepreneurial orientation on IACC, with social influence tested as a moderating variable. The findings reveal that technological, organizational, and environmental factors significantly affect SMEs’ intentions to adopt cloud computing, while social influence strengthens several of these relationships. The study concludes that enhancing managerial awareness and addressing security concerns can accelerate CCA. These findings offer valuable theoretical contributions and provide practical insights for policymakers and SME decision-makers in Kuwait and similar emerging economies.